Challenges and new opportunities on barrier performance of biodegradable polymers for sustainable packaging - Wu, Feng; Misra, Manjusri; Mohanty, Amar K. (Progress in polymer science, 2021)
Biodegradable polymers have emerged as a subject of enormous scientific and industrial interest due to their environmentally friendly compostability. For the benefit of the market economy and reoccurring environmental hazards, biodegradable materials should play a more critical role in packaging materials, which currently accounts for 60% of plastic products. However, various challenges remain for biodegradable polymers towards practical packaging applications. Particularly pertaining to the poor gas/moisture barrier issues which greatly limit the food packaging application of current biodegradable polymers. The chain architecture tailoring, crystallinity, melt blending/multi-layer co-extrusion, nanotechnology and surface coating have been considered as effective strategies for overcoming the poor gas/moisture barrier facing biodegradable polymers, which have been extensively researched for decades. In this review, we provide an in-depth study on the oxygen/water vapor barrier of representative biodegradable polymers in mainstream research with an emphasis on theoretical models and experimental modifications to improve their barrier properties. The influence of various strategies on the barrier improvement, and the pros/cons of each method are summarized. The limitations of current methods are discussed, and potential methods to overcome these limitations are presented. Finally, we conclude this review by listing current challenges associated with the barrier properties, processing and scalability of biodegradable polymers in the food packaging market, and future perspectives for these biodegradable polymers in sustainable composites field. [Display omitted]